SERVICE QUALITY E-BANKING PADA NASABAH BANK SYARIAH DI SURABAYA - Suryati Suryati (Jurnal Penelitian Administrasi Publik, 2021)
This study aims to identify the dimensions that play a role in the Service Quality of bank e-banking. The research scope is based on the research object, namely internet banking and mobile banking. Data collection was carried out in two stages. The first stage was interviews with 21 informants who had experience using e-banking, the second stage was distributing questionnaires to 42 to ask for opinions on the importance of Service Quality. The data analysis used qualitative and quantitative approaches, namely calculating the average. The results showed that there were 16 dimensions of service quality in the e-banking bank including the dimensions of availability, durability, accessibility, speed, convenience, on time, completeness of features, aesthetics, personnel, security, quality of information, accuracy of process, educative, relevant needs, communicative. , Caring Bank. The results of the research obtained are the rankings of each dimension of e-banking Service Quality in which Security and Convenience are dimensions of Service Quality that are of utmost importance to customers.